AB0753 Comparative study of systemic sclerosis with other autoimmune diseases for health-related quality of life. (12th June 2018) - Park, E.H.; Strand, V.; Oh, Y.J.; Kwon, H.; Song, Y.W.; Lee, E.B.
Abstract : Background: Systemic sclerosis (SSc) is a rare autoimmune disease characterised by fibrosis of the skin and multiple internal organ involvement. Previous studies reported a poorer health-related quality of life (HRQoL) in patients with SSc compared to the general population. However, very little is known about HRQoL of SSc as compared with other systemic autoimmune diseases, including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and Sjogren's syndrome (SJS) Objectives: To compare the HRQoL of patients with SSc and other systemic autoimmune disease and general population. Methods: HRQoL was captured by the Korean short form-36 health survey version 2 (SF-36), short form-6D (SF-6D) and 3 level version of EuroQol five-dimensional (EQ-5D) descriptive system (EQ-5D-3L). Between March and July 2017, consecutive patients with SSc, and randomly chosen patients with RA, SLE and SJS were recruited from the outpatient rheumatology clinics of Seoul National University Hospital, and were asked to answer SF-36 and EQ-5D. Disease activity of RA was evaluated by Disease Activity Score 28-ESR (DAS 28-ESR), SLE by Systemic Lupus Erythematosus Disease Activity Index-2k (SLEDAI-2k), and SJS by EULAR Sjogren's syndrome disease activity index (ESSDAI). For patients with SSc, Korean version of Health Assessment Questionnaire Disability Index (HAQ-DI) and Systemic sclerosis HAQ-DI (SSc HAQ-DI) were also evaluated. Demographic, clinical, laboratory information were obtained through a medical chart review. Data on representative Korean healthy controls were obtained from a study of psychometric properties of the Korean SF-36 v2 for assessing the general population, which was performed on six hundred healthy Koreans. Results: A total of 480 patients with SSc (n=120), RA (n=120), SLE (n=120) and SJS (n=120) and 600 healthy controls were included. The demographic features of patients were similar to the known features of each rheumatic disease group. Patients with rheumatic diseases had significantly lower SF-36 scores (p<0.001 in all domains), SF-6D scores (p<0.001), EQ-5D-3L index scores and EQ-VAS (p<0.001) than the healthy controls; adjustments for age and sex did not change those results. Patients with SSc showed significantly lower scores in the mental component summary scores compared with patients with RA (age and sex-adjusted scores, 43.0±0.9 vs 48.9±0.9; p<0.001). Specifically, domain of mental health was lower in SSc patients than RA patients (age and sex-adjusted scores, 61.3±1.8 vs 71.7±1.8, p<0.001). Among the physical domains scores, SSc patients showed lower score in general health domain than RA patients (age and sex-adjusted scores, 41.4±1.8 vs 51.3±1.8, p<0.001). Moreover, SSc patients reported remarkably lower scores of EQ-5D-3L index scores than all comparative rheumatic disease groups (RA, SLE, SJS) (p<0.001). HRQoL of patients with SSc was associated with HAQ-DI and SSc HAQ-DI. Conclusions: HRQoL of patients with systemic autoimmune diseases is significantly worse and affects all health domains in comparison to healthy controls. Patients with SSc have poorer HRQoL than patients with other rheumatic diseases. Specifically, SSc patients have more impaired mental health than RA patients, and the perception of an individual's general health is also poor compared to RA. Disclosure of Interest: None declared